Development and properties of bacterial cellulose, curcumin, and chitosan composite biodegradable films for active packaging materials. (15th May 2021) - Xu, Yixin; Liu, Xiaoli; Jiang, Qixing; Yu, Dawei; Xu, Yanshun; Wang, Bin; Xia, Wenshui
Graphical abstract: Highlights: CS, BC, and Cur are raw materials to develop biodegradable composites. CSn-BC-Cur composite films were prepared using a simple mixing method. The composite films presented satisfactory properties. The composite films displayed the best antioxidant activity. The composite films have potential application in food packaging area. Abstract: To deal with serious environmental damage resulting from plastic packaging materials, biodegradable films using natural products have gained considerable attention. Here, we provide a simple, fast, and environmentally-friendly route to construct a biodegradable film using chitosan (CS), bacterial cellulose (BC), and curcumin (Cur). Composite films (CSn-BC-Cur) using CS with different molecular weights were investigated, and their water moisture content (MC), water solubility (WS), contact angle (CA), mechanical properties, barrier properties, and antioxidant properties were compared. The obtained films were characterized by SEM, XRD, and TGA. The results showed that chitosan with a higher molecular weight presented higher contact angles and mechanical properties, along with a lower moisture content, water vapor transmission rate, and oxygen transmission rate. Furthermore, when the composite film was placed in 95 % ethanol, it released active substances. The results suggest that these composite films can be used as promising materials for food packaging.